Accounting for uncertainty from zero inflation and overdispersion in paleoecological studies of predation using a hierarchical Bayesian framework - Smith, Jansen; Handley, John C.; Dietl, Gregory P. (Paleobiology, 2021)
The effects of overdispersion and zero inflation (e.g., poor model fits) can result in misinterpretation in studies using count data. These effects have not been evaluated in paleoecological studies of predation and are further complicated by preservational bias and time averaging. We develop a hierarchical Bayesian framework to account for uncertainty from overdispersion and zero inflation in estimates of specimen and predation trace counts. We demonstrate its application using published data on drilling predators and their prey in time-averaged death assemblages from the Great Barrier Reef, Australia. Our results indicate that estimates of predation frequencies are underestimated when zero inflation is not considered, and this effect is likely compounded by removal of individuals and predation traces via preservational bias. Time averaging likely reduces zero inflation via accumulation of rare taxa and events; however, it increases the uncertainty in comparisons between assemblages by introducing variability in sampling effort. That is, there is an analytical cost with time-averaged count data, manifesting as broader confidence regions. Ecological inferences in paleoecology can be strengthened by accounting for the uncertainty inherent to paleoecological count data and the sampling processes by which they are generated.
CRIS-Team Scopus Importer:2021-09-24

Assessing the utility of death assemblages as reference conditions in a common benthic index (M-AMBI) with simulations - Smith, Jansen; Pruden, Matthew J.; Handley, John C.; Durham, Stephen R.; Dietl, Gregory P. (Geological Society of London, 2023)
Incorporating palaeontological data into the methods and formats already familiar to conservation practitioners may facilitate greater use of palaeontological data in conservation practice. Benthic indices (e.g. Multivariate-AZTI Marine Biotic Index; M-AMBI) already incorporate reference conditions and are a good candidate for integration. In simulations of living communities under constant and changing environmental con-ditions, we evaluate the capacity of death assemblage reference conditions to replicate M-AMBI values when used in place of reference conditions from the final ten generations of the simulation or all five hundred simulated generations. Reference conditions from all death assemblage scenarios successfully replicated correct remediation decisions in the majority of simulation runs with environmental change and stability. Variations in M-AMBI values were due to overestimated species richness and Shannon entropy values in the death assemblages but effects of changes to these parameters varied across scenarios, emphasizing the importance of evaluating multiple metrics. Time averaging was largely beneficial, particularly when environmental change occurred and short-term ecological observations (ten generations) produced incorrect remediation decisions. When the duration of time averaging is known, death assemblages can provide valuable longer-term perspectives with the potential to outperform temporally constrained baseline information from monitoring the living community.
CRIS-Team Scopus Importer:2024-12-16

BioDeepTime: A database of biodiversity time series for modern and fossil assemblages - Smith, Jansen; Rillo, Marina C.; Kocsis, Ádám; Dornelas, Maria; Fastovich, David; Huang, Huai Hsuan M.; Jonkers, Lukas; Kießling, Wolfgang; Li, Qijian; Liow, Lee Hsiang; Margulis-Ohnuma, Miranda; Meyers, Stephen; et al. (Global Ecology and Biogeography, 2023)
Motivation: We have little understanding of how communities respond to varying magnitudes and rates of environmental perturbations across temporal scales. BioDeepTime harmonizes assemblage time series of presence and abundance data to help facilitate investigations of community dynamics across timescales and the response of communities to natural and anthropogenic stressors. BioDeepTime includes time series of terrestrial and aquatic assemblages of varying spatial and temporal grain and extent from the present-day to millions of years ago. Main Types of Variables Included: BioDeepTime currently contains 7,437,847 taxon records from 10,062 assemblage time series, each with a minimum of 10 time steps. Age constraints, sampling method, environment and taxonomic scope are provided for each time series. Spatial Location and Grain: The database includes 8752 unique sampling locations from freshwater, marine and terrestrial ecosystems. Spatial grain represented by individual samples varies from quadrats on the order of several cm2 to grid cells of 100 km2. Time Period and Grain: BioDeepTime in aggregate currently spans the last 451 million years, with the 10,062 modern and fossil assemblage time series ranging in extent from years to millions of years. The median extent of modern time series is 18.7 years and for fossil series is 54,872 years. Temporal grain, the time encompassed by individual samples, ranges from days to tens of thousands of years. Major Taxa and Level of Measurement: The database contains information on 28,777 unique taxa with 4,769,789 records at the species level and another 271,218 records known to the genus level, including time series of benthic and planktonic foraminifera, coccolithophores, diatoms, ostracods, plants (pollen), radiolarians and other invertebrates and vertebrates. There are to date 7012 modern and 3050 fossil time series in BioDeepTime. Software Format: SQLite, Comma-separated values.
CRIS-Team Scopus Importer:2023-08-04
Keywords: deep-time; global; palaeobiology; species richness; temporal; timescale; turnover

Improving the relevance of paleontology to climate change policy - Kießling, Wolfgang; Smith, Jansen; Raja, Nussaïbah Begum (Proceedings of the National Academy of Sciences of the United States of America, 2023)
Paleontology has provided invaluable basic knowledge on the history of life on Earth. The discipline can also provide substantial knowledge to societal challenges such as climate change. The long-term perspective of climate change impacts on natural systems is both a unique selling point and a major obstacle to becoming more pertinent for policy-relevant bodies like the Intergovernmental Panel on Climate Change (IPCC). Repeated experiments on the impacts of climate change without anthropogenic disturbance facilitate the extraction of climate triggers in biodiversity changes. At the same time, the long timescales over which paleontological changes are usually assessed are beyond the scope of policymakers. Based on first-hand experience with the IPCC and a quantitative analysis of its cited literature, we argue that the differences in temporal scope are less of an issue than inappropriate framing and reporting of most paleontological publications. Accepting that some obstacles will remain, paleontology can quickly improve its relevance by targeting climate change impacts more directly and focusing on effect sizes and relevance for projections, particularly on higher-end climate change scenarios.
CRIS-Team Scopus Importer:2023-02-17
Keywords: biodiversity; climate change; IPCC; paleobiology

The Impact of Field Courses on Undergraduate Knowledge, Affect, Behavior, and Skills: A Scoping Review - Shinbrot, Xoco A.; Treibergs, Kira; Hernandez, Lina M. Arcila; Esparza, David; Ghezzi-Kopel, Kate; Goebel, Marc; Graham, Olivia J.; Heim, Ashley B.; Smith, Jansen; Smith, Michelle K. (Bioscience, 2022)
Field courses provide transformative learning experiences that support success and improve persistence for science, technology, engineering, and mathematics majors. But field courses have not increased proportionally with the number of students in the natural sciences. We conducted a scoping review to investigate the factors influencing undergraduate participation in and the outcomes from field courses in the United States. Our search yielded 61 articles, from which we classified the knowledge, affect, behavior, and skill-based outcomes resulting from field course participation. We found consistent reporting on course design but little reporting on demographics, which limits our understanding of who takes field courses. Cost was the most commonly reported barrier to student participation, and knowledge gains were the most commonly reported outcome. This scoping review underscores the need for more rigorous and evidence-based investigations of student outcomes in field courses. Understanding how field courses support or hinder student engagement is necessary to make them more accessible to all students.
CRIS-Team WoS Importer:2022-09-02